EVALUASI KINERJA SIMPANG TAK BERSINYAL TIPE 422 DAN TIPE 424M (STUDI KASUS : SIMPANG EMPAT TAK BERSINYAL JALAN TGH IBRAHIM KHOLIDI, KECAMATAN KEDIRI, KABUPATEN LOMBOK BARAT) - HASYIM HASYIM; ROHANI ROHANI (GANEC SWARA, 2023)
The unsignalized four-way intersection in Kediri is located in the Kediri Subdistrict of West Lombok Regency and is one of the unsignalized intersections situated very close to the center of community activities. Additionally, there is an educational center in the vicinity, and the traffic conditions at this intersection are quite congested on a daily basis. The mobility level of both individuals and goods, using both light and heavy vehicles, is visibly high at this intersection. A median strip is the central part of the road that physically separates opposing traffic flows. Therefore, the use of a median strip on the road significantly impacts traffic flow efficiency, by reducing delays, queue probabilities, side hindrances, decreasing accident rates, and providing comfort for road users, thereby making road users feel safe and organized. Thus, the government is planning to construct a road median.This study analyzes the performance of an unsignalized intersection before and after the installation of a median, covering aspects such as volume, side constraints, queue probabilities, delays, and saturation levels, using the 1997 Indonesian Highway Capacity Manual (MKJI) methodology.The analysis results for the unsignalized intersection before median installation show a capacity of 3061.5 vehicles per hour, a saturation level of 0.970 (Service Level D), a delay of 14.885 seconds per vehicle, a queue probability of 36.361%, and side constraints amounting to 881.9 incidents per hour. On the other hand, for the unsignalized intersection tipe after median installation, it exhibits a capacity of 3330.5 vehicles per hour, a saturation level of 0.729 (Service Level C), a delay of 12.654 seconds per vehicle, a queue probability of 21.942%, and side constraints amounting to 629.2 incidents per hour.The performance of the four-way intersection in Kediri on TGH Ibrahim Kholidi Road, in the Kediri Subdistrict of West Lombok Regency, was lower before the median installation compared to the tipe of intersection after median installation.